Developing a product service system for connected automated vehicles using quality functional deployment - Iz-Thaqyf s/o Mohamed Ismail (Nanyang Technological University, 2023)
The transportation sector has undergone significant changes due to the convergence of automotive, intelligence, and information technologies, which have given rise to innovative Connected and autonomous vehicles (CAVs). Suppliers such as automakers and IT companies have been promoting the development of CAVs, as they recognize the potential benefits of this technology. However, while some studies have explored the social and market acceptability of CAVs from an individual perspective, there is a research gap in understanding the relative importance of value attributes that could influence market success from both demand and supply perspectives.To address this research gap, we conducted a study using Quality Functional Deployment (QFD) to assess the different value attributes associated with CAVs. Our study aimed to identify and prioritize the benefits and concerns of CAVs from the perspectives of new potential vehicle owners. The QFD method enabled us to gather data from the emerging buyers and identify the relative importance of each attribute in terms of its impact on market success. This study has explored the means for developing a comprehensive product service System(PSS). This system aimed to enhance the user experience and provide added value to customers by incorporating advanced technology and digital solutions into the vehicle ownership experience. iv The findings of our study highlight the importance of understanding the different perspectives and priorities of stakeholders in the development and adoption of CAVs. The use of QFD as a research method enabled us to identify the key value attributes that could influence market success and to understand the relative importance of these attributes from both demand and supply perspectives. This information could be used to inform the development and marketing of CAVs and to improve their social and market acceptability.